Values and Symbol of Pujawali (Perang Topat) Tradition for Halal Tourism - Masniati Masniati (Universitas Muhammadiyah Mataram, 2018)
This study investigated the values and symbols within the traditional festival of Pujawali (Perang Topat) in West Lombok village of Lingsar and the relation between the values and symbols and tourism. The “perang” or war uses “ketupat” made from rice boiled in plaited coconut leaves as a weapon. The existence of the tradition nowadays becomes more popular. This tradition is not only about local celebration, but more about values and symbols beyond it. This study employed descriptive qualitative method, using interviews, observations and library research as techniques to collect data. The interviewees were the older members of two communities of Hindu and Muslim in Lingsar village. The finding indicated that Pujawali contains values, including historical, religious, and social values, and contains symbols of tolerance, brotherhood, and solidarity. The study suggests that the values and symbol which are represented in the traditional festival reflect the characteristics of Lingsar people—diverse but united.